IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE NHT DALAM PEMBELAJARAN MATEMATIKA - Khoiriyah, Siti (JURNAL e-DuMath, 2018)
One of the factors that influence student learning outcomes is the use of learning models in learning activities. Various learning models were tested by the teacher to see which learning model had the best effect on learning outcomes. Thus in this study, will see whether the mean student learning outcomes applied NHT learning model is better than the mean of student learning outcomes applied direct learning model. The populations in this study were seventh-grade students of MTs Nurul Falah. the Samplings were taken by cluster random technique. Data analysis is done by one-party and two-party t-tests. Based on the results of data analysis it was found that there were differences in the mean of student learning outcomes applied by the NHT model with them outcomes applied by the direct of learning model. The results of the analysis also showed that them outcomes applied by the NHT model were better than the mean student learning outcomes applied by the direct of learning model.